A new directed signature scheme on a general linear group over a group ring - MAKHLOUF, Sassia; Guenda, Kenza; Aaron Gulliver, Thomas (Journal of Innovative Applied Mathematics and Computational Sciences, 2023)
In this work, we propose a new directed digital signature scheme over a group ring whose security relies on the hardness of the discrete logarithm problem and the factorization search problem. This scheme is efficient as it requires very few operations for both signing and verifying signatures. Furthermore, the security of the proposed scheme is examined.